Photophysiological responses of the marine macroalga Gracilariopsis lemaneiformis to ocean acidification and warming. (January 2021) - Yang, Yuling; Li, Wei; Li, Yahe; Xu, Nianjun
Abstract: To study the combined effects of ocean acidification (OA) and warming on the growth and photosynthetic performance of the economically important marine macroalga Gracilariopsis lemaneiformis, thalli were grown under ambient low CO2 (390 μatm, LC) and elevated high CO2 (1000 μatm, HC) conditions with culture temperatures of 20 °C and 24 °C. Based on the evaluation of growth and photosynthetic responses to light and dissolved inorganic carbon (DIC), HC decreased the growth rate and phycoerythrin (PE) and phycocyanin (PC) levels but increased contents of UV-absorbing compounds (UVACs) in G. lemaneiformis at 20 °C, and high temperature counteracted these effects. Photosynthetic responses such as chlorophyll fluorescence parameters (maximum relative electron transport rate, rETRmax ; light use efficiency, α; saturation light intensity, Ik ; maximum quantum yield, FV /FM ; effective quantum yield, Y(II) and non-photochemical quenching, NPQ) were not different among the treatments. However, increased oxygen evolution (Pn ) and dark respiration (Rd ) rates were observed at 20 °C in the HC treatment. No significant effects of HC on apparent carboxylation efficiency (ACE), maximum oxygen evolution rate (Vmax ) and DIC affinity for oxygen evolution (K1/2DIC ) were found, and HC synergy with high temperature increased K1/2DIC . A lower C/N ratio with decreased tissue carbon but increased nitrogen was observed under HC and high-temperature treatment. Our results indicate that high temperature may counteract the negative effects of OA on the growth and pigment characteristics of G. lemaneiformis and improve food quality, as evidenced by enhanced N per biomass. Highlights: Warming counteracted the negative effects of OA on growth and pigmentations. OA synergy with warming showed down regulated CCMs. OA synergy with warming decrease tissue C but increase tissue N per biomass.